Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:8x+6−10x=−2(3x−1)
Step 1: Simplify both sides of the equation.
8x+6−10x=−2(3x−1)
8x+6+−10x=(−2)(3x)+(−2)(−1)(Distribute)
8x+6+−10x=−6x+2
(8x+−10x)+(6)=−6x+2(Combine Like Terms)
−2x+6=−6x+2
−2x+6=−6x+2
Step 2: Add 6x to both sides.
−2x+6+6x=−6x+2+6x
4x+6=2
Step 3: Subtract 6 from both sides.
4x+6−6=2−6
4x=−4
Step 4: Divide both sides by 4.
4x
4
=
−4
4
x=−1
Answer:
x=−1
Answer:
Step-by-step explanation:
The first step is the distribute the -2 over the parentheses, so it's:
8x + 6 - 10x = -2*3x + - 2* -1
8x + 6 - 10x = -6x + 2.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.